RANCANG BANGUN SISTEM INFORMASI DESA MENGGUNAKAN METODE SDLC BERBASIS WEB (STUDI KASUS DESA TAMAN JAYA) – SUKABUMI - Saeful Abdulloh Sayuti; Hani Fitriani Desi; Sri Wulansari; M. Azri Riyandi; Siti Olis; Sudin Saepudin (LPPM Universitas Nusa Putra, 2023)
This community service activity aims to socialize the use of technology in helping the wheels of government to be more advanced and developing and sustainable by assisting the provision of village website-based community services to assist and facilitate the community in accessing information. A case study of Tamanjaya Village located in Ciemas – Sukabumi district. The results of the service activities obtained are that in the Tamanjaya village itself there is no community service that provides information effectively and efficiently. For this reason, we provide solutions for the provision of website-based community services with the aim of facilitating access to information for the Tamanjaya village community in obtaining effective and efficient information.